Physicochemical Parameters Affecting the Distribution and Diversity of the Water Column Microbial Community in the High-Altitude Andean Lake System of La Brava and La Punta - Reynaldo Núñez Salazar; Carlos Aguirre; Jorge Soto; Pamela Salinas; Carlos Salinas; Humberto Prieto; Manuel Paneque (Microorganisms, 2020)
Due to the low incidence of precipitation attributed to climate change, many high-altitude Andean lakes (HAALs) and lagoons distributed along the central Andes in South America may soon disappear. This includes La Brava–La Punta, a brackish lake system located south of the Salar de Atacama within a hyper-arid and halophytic biome in the Atacama Desert. Variations in the physicochemical parameters of the water column can induce changes in microbial community composition, which we aimed to determine. Sixteen sampling points across La Brava–La Punta were studied to assess the influence of water physicochemical properties on the aquatic microbial community, determined via 16S rRNA gene analysis. Parameters such as pH and the concentrations of silica, magnesium, calcium, salinity, and dissolved oxygen showed a more homogenous pattern in La Punta samples, whereas those from La Brava had greater variability; pH and total silica were significantly different between La Brava and La Punta. The predominant phyla were Proteobacteria, Bacteroidetes, Actinobacteria, and Verrucomicrobia. The genera Psychroflexus (36.85%), Thiomicrospira (12.48%), and Pseudomonas (7.81%) were more abundant in La Brava, while Pseudospirillum (20.73%) and Roseovarius (17.20%) were more abundant in La Punta. Among the parameters, pH was the only statistically significant factor influencing the diversity within La Brava lake. These results complement the known microbial diversity and composition in the HAALs of the Atacama Desert.